Pendampingan Kemandirian Keluarga dalam Merawat Lansia di Dusun Candirejo Desa Awang-awang Kecamatan Mojosari Mojokerto - Andriyanto, Arief; Kusumaningrum, Umi Azizah; Sajidin, Muhammad; Wicaksono, Arif (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
The main focus of the community service program this time is fostering and increasing family independence in caring for the elderly. Elderly families are expected to be able to increase family independence in caring for the elderly at home. The first method of implementing the program using the "elderly polite family" approach is training and coaching of health cadres which will be carried out during 1 meeting. The service will involve students in carrying out these training and coaching activities. Next, a Focus Group Discussion will be held to find out the extent of the family's efforts to care for the elderly at home. The instrument uses the Apgar Family Score. The service results show that the p-value is 0.001 < 0.05. Based on decision-making in testing, it can be concluded that H1 is accepted, which means that there is effectiveness of the polite approach to elderly interventions on family independence in caring for the elderly. Elderly care needs to involve components to support the success of care, such as family and health cadres, as well as health workers in health services. Health workers must be able to choose what methods and media are given when carrying out nursing interventions.